Avaliação hepática em maçarico-rasteirinho (Calidris pusilla, LINNAEUS, 1766) durante o período de invernada no Nordeste Brasileiro - Silva, Edijanio Galdino da (2016)
Migratory birds suffer great physical and energy requirements, with the massive use of body energy reserves. Long distances can take migratory birds to dehydration and depletion of fat reserves. Furthermore, it is commonly observed decrease in weight of body, musculature, peritoneal fat and various organs. Some studies have found that liver and intestine also suffer from weight variation. Liver is an important organ for the assessment of the general state of migratory birds, providing valuable information about their physiological state, as it has important functions like metabolism of substances, glycogen storage, detoxification and synthesis of proteins, carbohydrates and lipids. The aim of this study was to determine whether there are significant differences in the assessment of Semipalmated Sandpiper (Calidris pusilla) liver in newly arrived birds in wintering site and birds in the middle of the wintering period in Northeast Brazil, emphasizing the evaluation of parameters of biochemical liver function, evaluation of liver composition, evaluation of deposition of hepatic glycogen and histopathologic analysis of liver tissue. The data revealed that there are significant differences in the liver composition, liver deposition of glycogen and liver histopathology findings, as well as the average values of serum albumin between the newly arrived birds and birds among the wintering period. Most of the findings were beneficial and showed that wintering sites are important areas for conservation of the species. Also, the negativity was found to Pasteurella spp., Mycobacterium spp. and Salmonella spp. as agents of hepatic granulomas observed in birds during the two periods analyzed. It is noteworthy that this is the first liver evaluation study in Calidris pusilla in wintering sites in Northeastern Brazil and it is expected that these results serve as subsidies for future studies related to the pathophysiology and investigation of potential etiological agents of liver injury observed.